Análise de artigos brasileiros sobre indisciplina, violência e ato infracional na escola : base Scielo 1998-2014 - Mello, Patricia de (Universidade Federal de São Carlos, 2015)
This work consists in a thesis and is intended to contribute to the educational system and the theoretical and practical advancement that interfaces between the two concepts, with support from the “dialogue” category. The researcher makes use of authors specialized in areas such as law and education to present reflections on the dialogical approach among them. Supported by the methodology of content analysis proposed by Bardin (2011), based on bibliographic research, seeks to demonstrate that progress toward better relations in school is more promising when it takes the path of dialogue. Thereby, adopts Freire’s theory as the theoretical reference of the study. The thesis is entitled “Analysis of Brazilian articles on indiscipline, violence and offenses at school: SciELO base 1998-2014”, because it identifies the actual reality inside the schools and the scholar community, that is exposed daily in the media. The question that is proposing to investigate is: what are the literature contributions that address the relationship between offense and indiscipline in schools, highlighting the mediation of the dialogue category? The aim of the research is to indicate literature contributions to address the relationship between offense and indiscipline in schools, by mediating the dialogue category. To do so, it was necessary to focus on the concepts of indiscipline, offenses and dialogues in school; highlighting, based on some of Freire’s works, concepts that contribute to the dialogic approach of the conflicts in schools; analyzing papers published in Brazilian journals of reference about the relationship established between indiscipline and offenses.
Keywords: Diálogo; Paulo Freire; Direito; Indisciplina; Ato infracional; Dialogue; Law; Indiscipline; Offenses; CIENCIAS HUMANAS::EDUCACAO